Appeasement and rewards: Explaining patterns of party responsiveness towards activist preferences. (March 2021) - Kaltenegger, Matthias; Heugl, Katharina; Müller, Wolfgang C
Intra-party democracy calls for party elites being responsive towards party activists. Yet, empirically, we know relatively little about how responsive parties are towards their rank and file and the factors influencing these processes. This article investigates drivers of party responsiveness towards activists, using a novel data source. Following a case study approach, the article analyses how motions submitted at 41 post-war party congresses of the Austrian Social Democratic Party were treated by party elites ( n = 3249). Results indicate that elite responsiveness is a means to appease activists when the party underperforms in party competition. Elites vary responsiveness across intra-party groups. They are more ready to accept the demands of those groups that are affected most by the party's failure to deliver. Party elites are also more responsive towards electorally successful subunits.